Case Report: IL2RA (CD25) deficiency: first reported cases in Morocco - Elamine, Ahamada; Benhsaien, Ibtihal; Errami, Abderrahmane; Bellarhrib, Yousra; Aadam, Zahra; Fahi, Mohammed; Bousfiha, Ahmed Aziz; El Bakkouri, Jalila; Ailal, Fatima (Frontiers in Immunology, 2026)
CD25, the α-chain of the interleukin-2 receptor (IL2RA), is a key component of the IL-2 pathway and is essential for the development and stability of regulatory T cells. Loss-of-function variants in IL2RA cause a very rare autosomal recessive disorder marked by early-onset autoimmunity and recurrent infections with an IPEX-like presentation. We report the first two molecularly confirmed cases of IL2RA (CD25) deficiency in Morocco, each carrying a distinct homozygous mutation. Both patients were born to first-cousin parents and presented in early childhood with recurrent respiratory and gastrointestinal infections, severe failure to thrive, chronic diarrhea with celiac-like enteropathy, and autoimmune manifestations including autoimmune hepatitis, dermatitis, and, in one case, autoimmune thyroiditis. Lymphocyte subset counts and immunoglobulin levels were within or above age-appropriate ranges, but flow cytometry showed a complete absence of CD25 expression on CD4+ T cells in both children, whereas relatives displayed intermediate levels compatible with carrier status. Targeted next-generation sequencing identified two novel IL2RA variants: a splice-site mutation (c.65-2A>G) and a multi-exon deletion (c.557_795-1625del), both leading to loss of functional CD25. Both variants were absent from population databases and classified as likely pathogenic or pathogenic according to ACMG criteria. These two cases expand the mutational and geographic spectrum of IL2RA deficiency and highlight the importance of considering this diagnosis in infants from consanguineous families who present with unexplained polyautoimmunity and recurrent infections. Simple flow cytometric assessment of CD25 on T cells is a valuable screening tool, and early genetic confirmation is crucial to guide timely hematopoietic stem cell transplantation and genetic counselling.